The Influence of Company Size, Funding Structure, Dividend Payout Ratio, and Profitability on Creative Accounting Behavior in Manufacturing Companies Listed on the IDX in 2020–2024 - Fidela Carissa Azaria (Return : Study of Management, Economic and Bussines, 2025)
This study aims to analyze the influence of firm size, capital structure, dividend payout ratio, and profitability on creative accounting behavior in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Creative accounting practices have gained significant attention as they can distort financial reporting, affect transparency, and reduce stakeholders' trust. A quantitative research design was employed, using multiple regression analysis to examine the relationship between these variables and creative accounting. The sample consisted of 30 manufacturing companies, selected through purposive sampling. The findings indicate that firm size and profitability have a significant positive influence on creative accounting behavior, suggesting that larger firms and those with higher profitability are more likely to engage in such practices. Conversely, capital structure and dividend payout ratio did not show significant effects. These results highlight the importance of regulatory oversight in addressing incentives for creative accounting, particularly in larger firms. The study offers theoretical contributions to accounting literature by identifying key determinants of creative accounting and provides practical implications for enhancing corporate governance and financial reporting transparency. It is recommended that regulators and companies adopt stronger governance frameworks to mitigate risks associated with creative accounting, thus fostering greater stakeholder trust.